Poesía y pintura. A propósito de Il suono impossibile della poesia. Rafael Alberti e la poesia dipinta de Loretta Frattale. - Ghignoli, Alessandro (Rassegna Iberistica - Università Ca' Foscari, 2020)
This article examines the multiple conformation that a poetic text maintains with other disciplines such as painting. We will analyse the different internal values of an openly dialogical writing in the production of the Andalusian poet Rafael Alberti, through a study by Loretta Frattale, Il suono impossibile della poesia. Rafael Alberti e la poesia dipinta. We will verify how a poem can be configured in a set of not only verbal but also visual perspectives, thus constructing a text, in the most semiological sense, that can be read in a continuous meeting of a verbovisual nature. This is a late Albertian move that prevails within the different writings of the Spanish poet.
Keywords: Alberti, Rafael - Crítica e interpretación; Literatura; Arte; Poesía; Pintura; Alberti; Frattale